Sex and Sexual Orientation Under Title VII of the Civil Rights Act of 1964: Same, Similar, or Distinct? - Lauren Abrams (Bellarmine Law Society Review, 2020)
Abrams delineates the arguments both for and against interpreting Title VII of the Civil Rights Act of 1964's protection from sex-based discrimination in the workplace to include sexual orientation as well. Drawing on precedent established in several landmark LGBTQ+ cases, Abrams sheds light on the inconsistency of judicial rulings regarding this issue. While her essay thoroughly explores the incentives and ramifications for the Court to proection against sexual orientation discrimination in the pending SCOTUS cases of Bostock v. Clayton County, Georgia and Altitude Express Inc. v. Zarda, Abrams ultimately argues that there is no replacement for the legislative branch's direct and unambigious modification of Title VII.